Relapsed Acinic Cell Carcinoma of the Parotid Gland With Diffuse Distant Metastasis - Yousef Khelfa MD, FACP; Munthir Mansour MD; Yousef Abdel-Aziz MD; Ali Raufi MD, FACP; Krista Denning MD; Yehuda Lebowicz MD (SAGE Publishing, 2016)
Acinic cell carcinoma (ACC) is an uncommon salivary gland neoplasm that generally displays an indolent growth pattern. Most cases arise in the major glands, particularly the parotid. However, it can arise from minor salivary glands in the oral cavity and aero-digestive tract. Although ACC is generally a low-grade malignant tumor, poorly differentiated and high-grade transformed variants exhibit a propensity for late recurrence and metastasis. There are no adequate clinical trials that define the optimal approach to patients with metastatic salivary gland tumors due to its rarity. Systemic therapy is reserved for cases where local therapy, such as radiation or metastasectomy, is not appropriate. Nevertheless, there is insufficient data in the literature regarding the chemotherapy of choice for metastatic ACC. In this article, we report a case of metastatic ACC of the right parotid gland that progressed on carboplatin and paclitaxel after partial response followed by doxorubicin and is currently on checkpoint inhibitor treatment.